2015
DOI: 10.1039/c5ta02504d
|View full text |Cite
|
Sign up to set email alerts
|

Porous imine-based networks with protonated imine linkages for carbon dioxide separation from mixtures with nitrogen and methane

Abstract: Porous imine-linked networks (PINs) have been prepared by catalyst-free Schiff base condensation of 2,4,6-(4-aminophenyl)1,3,5-triazine with 9,10-anthracene-dicarboxaldehyde (PIN1 and PIN1_2) and with 4,4 0 ,4 00 ,4 000 -methanetetrakis-benzaldehyde (PIN2). Even after synthesis optimisation, only with DMSO (PIN1 and PIN2) microporous frameworks were obtained, whereas DMF (PIN1_2) and other solvents led to nonporous systems, estimated by argon measurements. Furthermore, 15 N solid state NMR and IR spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 89 publications
3
69
0
Order By: Relevance
“…Besides, covalent triazine frameworks (CTFs) constitute a nitrogen-rich subclass of porous polymers, which are always used for CO 2 capture. [82][83][84][85] A CTFs (fl-CTF-350) was synthesized by ZnCl 2 both as "solvent" and Lewis acidic catalyst. 86 , respectively.…”
Section: Heteroatomic Skeletonmentioning
confidence: 99%
“…Besides, covalent triazine frameworks (CTFs) constitute a nitrogen-rich subclass of porous polymers, which are always used for CO 2 capture. [82][83][84][85] A CTFs (fl-CTF-350) was synthesized by ZnCl 2 both as "solvent" and Lewis acidic catalyst. 86 , respectively.…”
Section: Heteroatomic Skeletonmentioning
confidence: 99%
“…[15][16][17][18] It has been revealed that the properties of polymer depend mainly on the polymer architecture as well as the intrinsic properties of synthons. For example, the polymers comprising of larger conjugated system is of benefit to the adsorption of H 2 19,20 as well as the fluorescent detection of Nitro-benzene derivatives, while the polymers with large N content usually exhibits promoted adsorption affinity toward CO 2 .…”
mentioning
confidence: 99%
“…Synthesis of tetrakis(4‐formylphenyl)methane : A solution of tetrakis(4‐bromophenyl)methane (8.0 g, 12.58 mmol) in THF (250 mL) was cooled down to −78°C. Under stirring a solution of n ‐butyllithium (2.5 M in hexane, 50 mL, 125 mmol) was added dropwise.…”
Section: Methodsmentioning
confidence: 99%